THE RIGHT TO DISCONNECT AND PROTECTING WORKERS' MENTAL HEALTH IN THE DIGITAL AGE (CIPEEX, 2026)
This study analyzes the evolution of the Social Rule of Law in the face of the challenges posed by the digital age, with a focus on protecting workers' mental health. It argues that hyperconnectivity has resulted in a new form of precariousness, blurring the line between professional and personal life and generating exhaustion that recalls the dehumanization present in Kafka's “The Metamorphosis.” The work explores how the legal system, especially the 2017 Labor Reform, has gaps in the regulation of the right to disconnect, but demonstrates that case law has acted decisively to ensure the effectiveness of constitutional rights. The concept of existential damage and the role of the judiciary are analyzed from the perspective of counter-majoritarian difficulty, which, through judicial activism, has protected the dignity of workers. It concludes that the recognition of existential damage, illustrated by the TST's decision in Appeal No. 20509-83.2015.5.04.0811, and the questioning of exhausting work hours, such as the 6x1 shift, are imperative to adapt the law to the new times and ensure that technology does not undermine labor relations.
Keywords: social state of law; labor law; digital age; existential damage; countermajoritarian difficulty; judicial activism; employee mental health